DIABETIC FOOT LESIONS AND THEIR MANAGEMENT: Diabetic Foot Lesions - Haroun, Yousaf; Shukr, Irfan; Choudhry, Ahmed Khan; Hussain, Zakir (Pakistan Armed Forces Medical Journal, 2009)
Objective: To find out frequency of different types of diabetic foot lesions and different surgical procedures performed in our setup. Study Design: The study is a comparative study analyzing the efficacy of various surgical options for the treatment of diabetic foot lesions. Place and Duration of Study: The study was done at Combined Military Hospital Rawalpindi from July 2003 to July 2004. Patients and Methods: A total of 75 patients admitted with diabetic foot lesions were assessed in detail, and the various surgical procedures performed. After admission, history, general physical examinations and examination of the feet were carried out for hygiene, ulcers, gangrene, infection, hair loss, trophic changes in the skin and nails. Sensory and motor assessment and complete neurological examination was done. The patients were graded according to meggit wagner classification. Complete blood picture, serum blood glucose, urine for sugar and proteins, culture and sensitivity of pus, serum urea and creatinine and X-rays of foot in deep ulcer were done. Results: Out of the 75 patients male patients were effected more partly because they are more prove to trauma and mechanical stress of life. Out of 75 patients, 57 (76%) were male and 18 (24%) were female patients. Bulk of the patients were admitted through OPD (26) and emergency (16) total 56%, while other were either referred, transferred from peripheral hospitals, physicians or from other wards. Twenty eight patients were on Inj Insulin and 35 were on oral hypoglycemic drugs. The most common infecting agents were staphylococcus (42 patients) and pseudomonas in 28 patients. In majority of the patient incising and drainage of the abscess (12 cases) and toe nail extraction/removal in 11 patients were carried out. The commonest duration of patients in hospital stay was 8-20 days. Conclusion: The commonest lesion seen was infection and gangrene of the toes. Incision drainage, detriment and amputation of the toes were the common surgical procedures done. Most patients admitted for diabetic foot disease were in grade III and IV.